2020
DOI: 10.3390/informatics7020019
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Development of Competitive Translation Engines for Access to Multilingual COVID-19 Information

Abstract: Every day, more people are becoming infected and dying from exposure to COVID-19. Some countries in Europe like Spain, France, the UK and Italy have suffered particularly badly from the virus. Others such as Germany appear to have coped extremely well. Both health professionals and the general public are keen to receive up-to-date information on the effects of the virus, as well as treatments that have proven to be effective. In cases where language is a barrier to access of pertinent information, machine tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 18 publications
0
43
0
1
Order By: Relevance
“…The focus was on keywords, languages, and accounts to track. Way et al referred to Twitter posts to explain the need for automatic translation of COVID-19 knowledge bases [4]-the idea here is that the virus spreads in countries that use different languages. Vicari and Murru [5] discussed examples of irony in the Twitter posts that people posted in Italy at the beginning of the pandemic.…”
Section: Coronavirus On Twittermentioning
confidence: 99%
“…The focus was on keywords, languages, and accounts to track. Way et al referred to Twitter posts to explain the need for automatic translation of COVID-19 knowledge bases [4]-the idea here is that the virus spreads in countries that use different languages. Vicari and Murru [5] discussed examples of irony in the Twitter posts that people posted in Italy at the beginning of the pandemic.…”
Section: Coronavirus On Twittermentioning
confidence: 99%
“…In fact, this continuing focus on medically assisted dying has led to misrepresentations about the continuum of palliative care services and its access for diverse populations. A similar scenario is occurring in the context of the pandemic: resources are made available piecemeal rather than according to a sustainable long-term plan, resulting in misconstructions of the nature and extent of palliative care available, delays in receiving the needed care and an inability to make informed decisions about palliative care wishes (8,15).…”
mentioning
confidence: 98%
“…It has also highlighted acute inequities in the differential allocation of opportunities, practices, resources and policies. In this regard, a number of public health institutions, at a global level, reacted swiftly to inform the public about the unfolding of the pandemic, including specific and hard-to-reach populations, in a proactive manner with information in diverse languages (2,8). The pandemic has demonstrated that the public health responses of migrant host societies are deeply intertwined with policies as well as local rules and constraints (2,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations